Characteristics of School Culture in Inculcating Religious Values at SD Pusri Palembang - Ani Marlia (Borneo Educational Journal (Borju), 2023)
School culture is the foundation for presumptions, a system of values, beliefs, and habits, as well as the various types of products produced in schools that will encourage all school personnel to collaborate based on mutual trust, invite all citizens to participate, promote the emergence of new ideas, and present opportunities for implementing reforms in schools. Ideally, each school must have its own characteristics and policies to provide a good and religious environment in shaping students' character. However, many schools still do not pay much attention to school culture and the surrounding environment, so students' religious experience in learning is lacking. This study aims to describe the inculcation of religious values in elementary schools. This type of research is qualitative. The results of the study show that the religious values instilled in SD Pusri Palembang are the values of discipline, honesty, responsibility, tolerance, mutual respect, care for the environment, and sincerity. The inculcation of religious values is integrated in every subject, school culture and extracurricular activities. This study also shows that internal and external factors hinder the inculcation of religious values in students